Clinical assessment in disaster mental health: A logic of case formulation - McCabe, PhD, O. Lee; Kaminsky, MD, MBA, Michael J.; McHugh, MD, Paul R. (American Journal of Disaster Medicine, 2007)
Despite increased professional attention to the mental health aspects of disaster medicine in recent years, advances in clinical assessment of survivors of mass casualty incidents have been few. Contemporary assessment methods often yield little more than check lists of symptoms that, while they may lead to reliable DSM-IV diagnoses, provide no sense of the individual patient’s plight and so are inadequate for case formulation, treatment planning, and prognosis estimation. The authors describe a comprehensive model for assessing patients developed at the Johns Hopkins Department of Psychiatry and Behavioral Sciences. Relating it to the field of disaster mental health for the first time here, the approach uses four distinct but overlapping appraisal perspectives, each of which drives a set of exploratory propositions and leads to an understanding of the essential natures of clinical disorders and their underlying etiologies. The perspectives address the following: (a) what the individual “has” (biologically based disease and physical illness); (b) who the individual “is” (graded dimensions of temperament, disposition, traits, intelligence, etc); (c) what the individual “does” (purposeful, goal-directed, conditioned behavior, etc); and (d) what the individual “has encountered” (his/ her life story and the meaning that has been given to those experiences). Following a description of each perspective from the standpoint of its underlying logic, inquiry domain, and indicated intervention, the authors highlight the potential hueristic value of the model by illustrating numerous testable hypotheses that can be generated through the juxtaposition of the four assessment perspectives with three longitudinal considerations for the management of trauma patients, ie, the stress-related constructs of (pre-incident) resistance, (peri-incident) resilience, and (post-incident) recovery.